Socioeconomic and Family Determinants of Primary School Pupils’ Academic Performance in Osun State, Nigeria - Gbenga-Akanmu, Taiwo Oladunni; Oladunni, Adedoyin Iyanuoluwa (EDUPEDIA Publisher, 2026)
Purpose – This study examined the factors affecting the academic performance of primary school pupils in Osun State, Nigeria. Specifically, it investigated the influence of parents’ socioeconomic status, educational background, occupation, parenting styles, and family structure, size, and background on pupils’ academic performance. Methodology – The study adopted a correlational descriptive survey design. A multistage sampling procedure was used to select 100 pupils from four Local Government Areas across the senatorial districts of Osun State. Four schools were selected from each LGA, comprising both private and public schools, and 25 pupils were randomly selected from each school. Data were collected using the Pupils’ Questionnaire on Academic Performance and Socioeconomic Status of Parents (PQAPSSP). The instrument’s reliability was established using Cronbach’s alpha, which yielded 0.78. Data were analyzed using frequency distribution tables and decision rate. Findings – Five major factors positively influenced pupils’ academic performance: authoritative parenting style, small class size, adequate school resources, stable parental occupation, and nuclear family structure. The absence of these factors was associated with poor academic performance. The study further showed that parents’ socioeconomic status significantly contributed to pupils’ cognitive development and academic success. Novelty – This study contributes to the existing literature by providing empirical evidence on the correlation between parental socioeconomic status and pupils’ academic performance in Osun State. Significance – The findings would benefit pupils, parents, teachers, educational planners, and other stakeholders seeking to improve academic performance in primary schools.